Improving food-system efficiency and environmental conservation using agricultural biodiversity in Busia County: a pilot study - Manjella, A.; Wasike, Victor W.; Borelli, Teresa; Hunter, D. (Elsevier, 2018)
BackgroundDespite the abundance of edible biodiversity, both wild and cultivated, malnutrition and food insecurity persist in Busia County, Kenya, where poverty indices range from 63% to 74% and 25% of children younger than 5 years are stunted, 11% are underweight, and 4% are thin for their age. Much of this biodiversity, used in traditional food preparations, has the potential to provide access to key micronutrients for healthy and balanced diets and to act as an important source of community resilience to climate change and economic turbulence. Yet, low consumer awareness of the value of local biodiversity, poorly developed value chains, and negative perceptions of traditional foods have led to the disappearance of many nutrient-rich species and the shift to unhealthy diets. We aimed to show that heightened knowledge of the value of biodiversity and improved value-chain efficiencies can help to conserve biodiversity and improve local food systems.MethodsWe developed a farmer business school model and provided training to 25 farmer groups across seven sub-counties in Busia County, Kenya, on the sustainable production of traditional vegetables, post-harvest handling, contract farming, nutrition, and value addition. We also analysed selected species for nutritional content, tested a food procurement model supporting market linkages between farmers and local institutions, and carried out nutrition education activities to improve the capacity of schools and clinics to incorporate traditional foods into meals.FindingsWe found that traditional vegetables were rich in iron—for example, cowpea leaves contained 17 times more iron than did kales. After making the nutritional data available to all value chain actors during implementation of the food procurement model, we recorded a 12% increase in the number of households cultivating local biodiversity, both for household consumption and off-farm sales, along with a 75% increase in the plot size devoted to traditional vegetable cultivation. Furthermore, household incomes increased by a mean of 47% (SD 30) as a result of direct links with institutional markets. The effects of increased market linkages on education, economic, and health benefits will be measured in a second phase of the project to start in 2018.InterpretationThe project has positively affected the abundance, composition, and distribution of species and revived interest in local food biodiversity, in addition to producing benefits around diverse diets. Experience in implementing the Busia model has been used to inform global policies that aim to mainstream biodiversity in sustainable food systems using public procurement, particularly schools, as a platform for improving nutrition. Nationally, a biodiversity policy was developed for Busia County that recognised the importance of local biodiversity, including for improved livelihoods, community resilience, and health and nutrition.FundingGlobal Environment Facility, Australian Centre for International Agricultural Research, and the MacArthur Foundation.